ANALYSIS OF FACTORS AFFECTING EMPLOYEE PERFORMANCE - I Nyoman Tri Sutaguna; Titin Endrawati; Adrian Febriana Dima; Harfiahanj Indah Rakhma Ningtyas; Rinovian Rais (Bajang Institute, 2022)
The purpose of this study to discuss about analysis of factors affecting employee performance. In this study, researchers used a type of causal associative research with a quantitative approach. In this study, the population will be employees, totaling 85 people. If the total population is less than 100 people, then the total number of samples taken is 85 people as the sample of this study. The analytical method uses multiple linear regression analysis. The research results show that motivation has a positive and significant effect on employee performance. Leadership has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance